Neuromodulation of Mu Opioid Receptor (MOR-1) Gene (OPRM1) Alternatively-Spliced Variants Following Exposure to Morphine with Alma Fig (Ficus carica) Leaf Extract in Human Neuroblastoma (SH-SY5Y) Cells: Review (Global Journal of Medical Research, 2020)
The role of morphine in regulating the mu-opioid receptor (MOR-1) relative to pain is well-established. Efforts are ongoing to elucidate the pharmacological significance of newly identified MOR-1 alternative splice variants. Aberrant splicing events have been implicated in a growing number of diseases, including cancer, but it is uncertain whether any pharmacological benefit may be derived from the use of these variants. Chronic use of opioids yields tolerance, withdrawal, and potentially fatal addiction. With current interests so high on developing marijuana as a marketable drug, there is concern whether its introduction as a mainstay may interfere with pain medications, such as opioids, for which there is a growing concern of epidemic proportions. We, therefore, hypothesized that the introduction of traditional herbal medicines while taking morphine would interfere with normal pain receptor functions. We tested this hypothesis by chronically (48hrs) exposing human neuroblastoma (SH-SY5Y) cells to a pain medication (morphine) followed by a natural herb, and measuring its effect on the expression of MOR-1 alternatively-spliced variants. (RA)-differentiated human neuroblastoma (SH-SY5Y) cells treated with morphine (10 #x3BC;M), fig leaf extract (3 #x3BC;L/30 mL media), or both for 48 hours, were analyzed by quantitative real-time polymerase chain reaction (qRT-PCR) using the Bio-Rad iCycler/MyiQ#x2122;. Of the seven fig (Ficus carica L.) cultivars (Green Ishia, Brown Turkey, Mission, Alma, Giant Celeste, Nero, Hollier) identified for this pilot study, Alma fig leaf extract was selected for combined therapy with morphine. Statistically significant differential regulation of MOR-1 alternative splice variants was widely observed in control, morphine, Alma fig leaf extract, and morphine/Alma fig samples. The results of this pilot study confirm our hypothesis that MOR-1 splice variants are differentially regulated following chronic exposure to morphine and Ficus carica. Further examination of the relationship between morphine and herbs used in traditional medicine may enhance our understanding of the mechanistic basis of morphine tolerance and may give clues concerning the therapeutic benefit of using Ficus carica Author #x3B1; #x3C3; #x3C1; : Basic
Keywords: Ficus carica; G-protein; mu-opioid receptor; opioid; morphine; tolerance; alternative splicing